Experimentally induced colitis impacts myelin development and home-cage behavior in young pigs regardless of supplementation with oral gamma-cyclodextrin-encapsulated tributyrin - Sutkus, Loretta T.; Sommer, Kaitlyn M.; Li, Zimu; Sutton, Bradley P.; Donovan, Sharon M.; Dilger, Ryan N. (Frontiers in Neuroscience, 2025)
IntroductionColitis, a chronic intestinal disorder that causes inflammation of the colonic mucosa, has been linked with structural brain abnormalities. To combat intestinal inflammation, researchers have investigated how nutritional supplementation, such as butyric acid, may ameliorate untoward effects. By encapsulating and using conjugates of butyrate, such as butyrate glycerides (i.e., tributyrin), slower release to the lower portions of the gastrointestinal tract can be achieved. Additionally, butyrate supplementation has been linked with supporting brain function and regulating integrity.MethodsIn the present study, a total of 24 intact male pigs were artificially reared and randomly assigned to 1 of 3 treatment conditions: (1) a control milk replacer (CON), (2) control plus oral dextran sodium sulfate (DSS) to induce colitis, or (3) control supplemented with 9.0 mM of gamma-cyclodextrin encapsulated tributyrin (TBCD) plus oral DSS (TBCD+DSS). Pigs were orally administered DSS treatments daily from postnatal day (PND) 14–18. Continuous video recording began on PND 3 and ceased on PND 27 or 28, with videos processed and analyzed for home-cage tracking behavior. On PND 26 or 27, pigs underwent neuroimaging procedures to assess overall brain anatomy (MPRAGE), microstructure (DTI), and myelin (MWF).Results and discussionHome-cage spatial preference was not altered prior to DSS dosing or during the overall study period. However, TBCD+DSS pigs spent less (p < 0.05) time within quadrant 4 when compared with CON pigs. Across almost all 29 brain regions assessed, absolute volumes were observed to be smaller in the TBCD+DSS group compared with CON and DSS groups. However, once individual volumes were assessed relative to the whole brain, most treatment effects dissipated other than for gray matter volume (p = 0.041). Diffusivity was found to be altered in several regions across treatment groups, thereby indicating differences in fiber organization. In areas like the hippocampus and thalamus, when fractional anisotropy (FA) values were highest for a given treatment, in the other diffusion metrics (mean, radial, axial diffusivity) values were lowest for that same treatment, indicating more organized cellular structure. Several other diffusion trends and differences were observed across various regions. Lastly, myelin water fraction (MWF) values were lowest in DSS-treated groups compared with CON (p < 0.05) for the whole brain and left/right cortices.ConclusionOverall, fiber organization and myelination were observed to be altered by experimentally induced colitis and contrary to expectations, tributyrin supplementation did not ameliorate these effects. Future work is warranted to investigate other protective nutritional mechanisms for colitis.